Protective Effect of Alcoholic extract of Black Current in Male Reproductive System of Methionine Overload Rats - Al-Okaily, Baraa Najim (The Iraqi Journal of Veterinary Medicine, 2012)
This study was undertaken to investigate the deleterious- effect of methionine overload on male reproductive system of adult male rats. It was also aim to studying the beneficial protective effect of alcoholic extract of black current. Eighteen adult male rats (175-200 gm) were used, animals were randomly divided into three groups (6/group) and were treated daily for 42 days as follows: 1-Group C (control); 2- group I(GI), the rats in this group were orally intubated by gavages needle DL-methionine (100 mg / Kg BW.) 3- animals in group II(GII) were administered orally alcoholic extract of black current (60 mg /Kg BW.) in addition to methionine. At the end of the experiment blood samples were collected for measuring serum testosterone (T) hormone and follicular stimulating hormone (FSH) concentrations. As well as histological section, for testis was taken for histopathological study the results revealed that oral intubation of 100mg /kg BW. of methionine for 42 days caused significant decrease - in serum testosterone (T) hormone and follicular stimulating hormone (FSH) concentrations in groups (GI and GII) comparing to control ,while oral intubation of alcoholic- extract of black current (GII) caused significant elevation in the concentration of these two hormones comparing to methionine treated group (GI). Furthermore, methionine intubation caused significant decrease in diameter and thickness of seminiferous tubules with cellular degeneration of Sertoli cells, while black current intubation caused significant increase in the previous criteria and regeneration of Sertoli cells. In conclusion, this study pointed to the deleterious effect of methionine overload and assures protective effect of alcoholic extract of black current on adult male rats reproductive system.